TREATMENT OUTCOMES OF KIDNEY STONES USING MINI-PERCUTANEOUS NEPHROLITHOTOMY AT VINMEC TIMES CITY INTERNATIONAL GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the outcomes of kidney stone treatment using mini-percutaneous nephrolithotomy at Vinmec Times City International General Hospital.Subjects and methods: A descriptive, cross-sectional study was conducted involving 48 patients undergoing mini-percutaneous nephrolithotomy in the lateral decubitus position for kidney stone treatment from January 2022 to May 2025 at the Department of Urology, Vinmec Times City International General Hospital.Results: The mean age of patients was 55.2 ± 13.5 years. The mean stone size on computed tomography was 28.04 ± 8.6 mm, the group of stones < 20 mm accounted for 12.5%, while the group of stones ≥ 20 mm accounted for 87.5%. Single stones were present in 54.2% of cases, while multiple stones (≥ 2) accounted for 45.8%. The mean operative time was 89.17 ± 33.5 minutes. The stone-free rate after the first surgery was 79.2%. The complication rate was 12.5%, including postoperative bleeding not requiring transfusion (4.2%) and urine leakage through the drainage tract (8.3%). Postoperative outcomes were classified as good in 68.8%, moderate in 31.3%, with no poor outcomes reported.Conclusion: Mini-percutaneous nephrolithotomy at Vinmec Times City International General Hospital is a minimally invasive, safe, and effective technique with a high stone clearance rate for kidney stone treatment.
Keywords: Kidney stones, mini-percutaneous nephrolithotomy.